Prdm9 Intersubspecific Interactions in Hybrid Male Sterility of House Mouse. (8th July 2020) - Mukaj, Amisa; Piálek, Jaroslav; Fotopulosova, Vladana; Morgan, Andrew Parker; Odenthal-Hesse, Linda; Parvanov, Emil D; Forejt, Jiri
Abstract: The classical definition posits hybrid sterility as a phenomenon when two parental taxa each of which is fertile produce a hybrid that is sterile. The first hybrid sterility gene in vertebrates, Prdm9, coding for a histone methyltransferase, was identified in crosses between two laboratory mouse strains derived from Mus mus musculus and M. m. domesticus subspecies. The unique function of PRDM9 protein in the initiation of meiotic recombination led to the discovery of the basic molecular mechanism of hybrid sterility in laboratory crosses. However, the role of this protein as a component of reproductive barrier outside the laboratory model remained unclear. Here, we show that the Prdm9 allelic incompatibilities represent the primary cause of reduced fertility in intersubspecific hybrids between M. m. musculus and M. m. domesticus including 16 musculus and domesticus wild-derived strains. Disruption of fertility phenotypes correlated with the rate of failure of synapsis between homologous chromosomes in meiosis I and with early meiotic arrest. All phenotypes were restored to normal when the domesticus Prdm9 dom 2 allele was substituted with the Prdm9 dom2H humanized variant. To conclude, our data show for the first time the male infertility of wild-derived musculus and domesticus subspecies F1 hybrids controlled by Prdm9 as the major hybrid sterility gene. The impairment of fertility surrogates, testes weight and sperm count, correlated with increasing difficulties of meiotic synapsis of homologous chromosomes and with meiotic arrest, which we suppose reflect the increasing asymmetry of PRDM9-dependent DNA double-strand breaks.